Hepatic angiosarcoma as a cause of acute liver failure - Singh, Gurpreet (BMJ Case Rep, 2018)
Hepatic angiosarcoma is an extremely rare disease entity that accounts for approximately 0.1%–2% of primary liver malignancy. It is three times more common in men than women and usually affects the former in their sixth or seventh decade of life. Risk factors for the development of hepatic angiosarcoma include the use of oral contraceptives, exposure to anabolic steroids, radiation, thorium dioxide, arsenic and vinyl chloride. The prognosis of hepatic angiosarcoma is extremely poor which is attributable to early metastases to other organs, resistance to traditional chemotherapy and radiotherapy regimens and rapid progression of the tumour. Optimal management of patients is poorly demarcated due to the rarity of the tumour. We present a case series of two patients: one who passed away due to acute hepatic failure secondary to hepatic angiosarcoma and the second who underwent a liver transplantation and was subsequently diagnosed with hepatic angiosarcoma based on his explant histology.